2014
DOI: 10.1039/c4fo00469h
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chitosan oligosaccharide (GO2KA1) supplementation on glucose control in subjects with prediabetes

Abstract: We aimed to evaluate the effect of chitosan oligosaccharide (GO2KA1) supplementation on glucose control in subjects with prediabetes. This study was a randomized, double-blind, placebo-controlled clinical trial. Subjects with prediabetes were randomly assigned to the GO2KA1 intervention group or the placebo group for 12 weeks. We assessed the serum levels of glucose, insulin, and C-peptide by a 2 hour value in the 75 g oral glucose tolerance test (OGTT), HbA1c, pro-inflammatory cytokines, and plasma adiponecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 39 publications
2
42
0
1
Order By: Relevance
“…This observation may indicate that GO2KA1 acts as a PPARγ ligand as rosiglitazone but the affinity to PPARγ may be weaker than the synthetic drug or GO2KA1 may mediate auto‐downregulation of PPARγ in a yet unidentified mechanism. It is important to note that increased adiponectin expression in adipocytes is consistent with our clinical observation that GO2KA1 supplementation increased plasma adiponectin level concomitant with improved glucose tolerance in prediabetic patients .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This observation may indicate that GO2KA1 acts as a PPARγ ligand as rosiglitazone but the affinity to PPARγ may be weaker than the synthetic drug or GO2KA1 may mediate auto‐downregulation of PPARγ in a yet unidentified mechanism. It is important to note that increased adiponectin expression in adipocytes is consistent with our clinical observation that GO2KA1 supplementation increased plasma adiponectin level concomitant with improved glucose tolerance in prediabetic patients .…”
Section: Resultssupporting
confidence: 87%
“…Also, this postprandial blood glucose‐lowering effect was confirmed in healthy individuals who received oral sucrose tolerance test . Furthermore, GO2KA1 supplementation significantly reduced postprandial glucose absorption with increased plasma adiponectin levels in our intervention study. However, the underlying mechanisms by which GO2KA1 suppresses the absorption of glucose into the blood stream and increases plasma adiponectin levels still remain unclear.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…We hypothesized that a similar reduction in OGTT glucose levels at 120 minutes would be observed after AF treatment among the target population in this study, which is considered clinically meaningful [13]. Power analysis indicated that a total sample of 40 subjects, 20 in each group, would be required to detect a 19.24 mg/dL reduction in glucose at 120 minutes, with a significance level of 0.05 and at least 80 % power.…”
Section: Methodsmentioning
confidence: 99%
“…A number of publications have been devoted to the antidiabetic effect of COS. For instance, low molecular weight COS has the potential for hyperglycemia management and provides a strong rationale for T2DM prevention via COS 17. COS can help control postprandial glucose in subjects with prediabetes 18. COS demonstrates its antidiabetic effect by inhibiting the expression of intestinal α-glucosidase, glucose transporters, and peroxisome proliferator-activated receptor γ 19.…”
Section: Introductionmentioning
confidence: 99%